SISTEM MONITORING TECHNICAL SUPPORT DIVISI CORE NETWORK OPERATION DI PT. TELKOMSEL SEMARANG (Information Technology and Telematics, 2015)
Abstract-- PT . Telkomsel Semarang require Human Resources ( HR ) non- organic or non-permanent employees ( outsourced ) as an honorary auxiliary personnel stationed in several divisions in PT . Telkomsel Semarang , especially in the division CORE NETWORK OPERATION ( CNO ) .                    Division CNO has auxiliary personnel assigned to support the performance of the telecommunications device that operates 24 hours a day . Therefore, the presence of highly influential presence in the performance of the auxiliary power .Through Monitoring System Technical Support Division Core Network Operations at PT . TELKOMSEL Semarang , can help supervisors to monitor technical support and can help improve the performance of the work of the technical support division of Core Network Operations at PT .Keywords-- Monitoring System Technical Support , Core Network Operation Division at PT . TELKOMSEL Semarang